Quantitative liver SPECT/CT is a novel tool to assess liver function, prognosis, and response to treatment in cirrhosis - Kaur, Amritjyot; Verma, Nipun; Singh, Baljinder; Kumar, Ajay; Kumari, Sunita; De, Arka; Sharma, Ratti Ram; Singh, Virendra (Frontiers in Medicine, 2023)
Background: Functional liver reserve is an important determinant of survival in cirrhosis. The traditional indocyanine green test (I.C.G.) is cumbersome. Hence, we developed and validated a novel liver imaging, a hybrid of SPECT and CT (Q-SPECT/CT), for evaluating disease severity, outcomes, and response to treatment in decompensated cirrhosis (D.C.). Methods: We recruited a cohort of DC patients at a tertiary institute between 2016-2019. First, we standardized the Q-SPECT/CT across a predefined range of volumes through phantom experiments. Then we performed clinical and laboratory evaluations, I.C.G. test (retention at 15 minutes), and Q-SPECT/CT at baseline and 12 months of granulocyte colony-stimulating factor (G-CSF) and standard medical treatment (S.M.T). Results: In 109 DC patients, 87.1% males, aged 51±10 years, MELD: 14(7-21), the quantitative liver uptake (%Q.L.U.) on Q-SPECT/CT exhibited a strong correlation with C.T.P. (r=-0.728, p<0.001), MELD (r=-0.743; p<0.001) and I.C.G.-R-15 (r=-0.720, p<0.001) at baseline. %Q.L.U. had the maximum discrimination (A.U.C.: 0.890-0.920), sensitivity (88.9-90.3%), specificity (81.2-90.7%), and accuracy (85.8-89.4%) than liver volumes on Q-SPECT/CT or I.C.G. test for classifying patients in CTP/MELD based prognostic categories. A significant increase in %Q.L.U. (26.09±10.06 to 31.2±12.19, p=0.001) and improvement in CTP/MELD correlated with better survival of G-CSF treated D.C. patients (p<0.05). S.M.T. did not show any improvement in Q-SPECT/CT or clinical severity scores (p>0.05). %Q.L.U.>25 (adj.H.R.: 0.234, p=0.003) and G-CSF treatment (adj.H.R.: 0.414, p=0.009) were independent predictors of better 12-months survival in D.C. Conclusion: Q-SPECT/CT (%Q.L.U.) is a novel non-invasive, diagnostic, prognostic, and theragnostic marker of liver reserve and its functions in cirrhosis patients.